2010
DOI: 10.1111/j.1365-2583.2010.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Two novel Salp15‐like immunosuppressant genes from salivary glands of Ixodes persulcatus Schulze tick

Abstract: Salp15, a 15-kDa tick salivary gland protein, is known for several suppressive activities against host immunity and critical functions for the transmission of Lyme borrelia in Ixodes scapularis and Ixodes ricinus, the major vectors found in North America and Western Europe. Salp15 inhibits the activation of cluster of differentiation (CD)4(+)T-cells through the repression of T-cell receptor (TCR)-triggered calcium fluxes and interleukin (IL)-2 production. Furthermore, Salp15 adheres to the spirochaeta and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…exploits the salp15 tick protein and is able to induce its expression in order to facilitate mammalian host infection. Based on these results reported for Borrelia [48], [49], it is then possible to speculate that Bartonella sp. are also capable of increasing the production of some of the salp15 proteins to facilitate their transmission to the vertebrate host.…”
Section: Salp15 Super-family Proteinsmentioning
confidence: 72%
“…exploits the salp15 tick protein and is able to induce its expression in order to facilitate mammalian host infection. Based on these results reported for Borrelia [48], [49], it is then possible to speculate that Bartonella sp. are also capable of increasing the production of some of the salp15 proteins to facilitate their transmission to the vertebrate host.…”
Section: Salp15 Super-family Proteinsmentioning
confidence: 72%
“…Evidence was also provided that the pathogen B. burgdorferi in I. scapularis exploits Salp15 during transmission to a vertebrate host, as it specifically interacts with B. burgdorferi outer surface protein C (OspC) and the binding of Salp15 protects B. burgdorferi from antibody-mediated killing in vitro (Ramamoorthi et al, 2005). Salp 15-like sequences encoding proteins of the Salp family have also been identified in salivary glands of Ixodes pacificus, I. ricinus , and I. persulcatus , which are other major vectors of disease agents in the USA and Eurasia (Hovius et al, 2007; Hojgaard et al, 2009; Mori et al, 2010). The results suggest that the Salp15 homologues can be involved in host immunomodulation and transmission of Borrelia species in the above regions.…”
Section: Tick Salivary Compounds and Host Immune Responsesmentioning
confidence: 99%
“…The known Salp15 sequences were predicted to contain a signal peptide in their N-terminus which would be cleaved during protein expression [18], [27], [28], [36] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Because of these properties, scientists have suggested that Salp15 could be a potential target for the development of vaccines against Lyme spirochetes [24], [25], [26]. Recently, Salp15 homologues have been characterized from some species in the Ixodes ricinus complex in different parts of the world [14], [18], [27], [28]. However, no comparable information is available on Salp15 in Ixodes persulcatus and I. sinensis , two members of the Ixodes ricinus complex from China.…”
Section: Introductionmentioning
confidence: 99%